Pendampingan “Pembuatan Foto Produk” Pada Marketplace Bagi UMKM RW 09 Kelurahan Pandean Lamper, Kecamatan Gayamsari, Kota Semarang - Adinda Tifany Putri; Bayu Teguh Wicaksono; Reggy Afrio Artama; Donny Afriyandi; Veronica Aurora Putri; Anastasya Tri Utami; Birgita Erica; Mizanul Kharir (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Within SMEs, photography is an important part of the promotion and marketing concept in the modern era. The results presented by photographic works help build the reputation of the merchandise. Photography can strengthen the competition strategy between products in the virtual digital era. Pandean Lamper is one of the sub-districts in Gayamsari District, Semarang City. Pandean Lamper Village has superior products produced by Micro, Small and Medium Enterprises (MSMEs). Activities promoting these products can support the economy of local residents, one of which is taking attractive product photos. Attractive product photos don't have to use expensive and sophisticated equipment. An understanding of photography tricks and techniques for taking product photos is an important part of attracting consumer attention which is carried out by students of the Communication Studies Program, University of Semarang. The results of the evaluation monitoring carried out during the activity were an increase in the skills of MSME actors in the Pandean Lamper Village, in the use of photography techniques to take good and attractive product photos.